MODEL PENGEMBANGAN KURIKULUM BERBASIS PADA TEORI-TEORI PENGEMBANGAN KURIKULUM INDONESIA DAN DUNIA ISLAM (MALAYSIA, MESIR, DAN MAROKO) - Firmadeli Firmadeli; Rahma Hazalia (Ensiklopedia of Journal, 2026)
This study aims to examine curriculum development models based on curriculum development theories applied in Indonesia and other Islamic countries such as Malaysia, Egypt, and Morocco. The research method used is a literature study by collecting and analyzing various relevant literature. The results of the study show that curriculum development in these four countries has similarities in integrating Islamic values with a modern approach, but there are differences in terms of locality, the role of the government, and the role of society in it. The implications of these findings can be used to recommend more adaptive and inclusive curriculum development strategies in the future.Keywords: Curriculum Theory, Curriculum Development, Islamic World